150m-75m+43200=45450+150m

Simple and best practice solution for 150m-75m+43200=45450+150m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 150m-75m+43200=45450+150m equation:


Simplifying
150m + -75m + 43200 = 45450 + 150m

Reorder the terms:
43200 + 150m + -75m = 45450 + 150m

Combine like terms: 150m + -75m = 75m
43200 + 75m = 45450 + 150m

Solving
43200 + 75m = 45450 + 150m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-150m' to each side of the equation.
43200 + 75m + -150m = 45450 + 150m + -150m

Combine like terms: 75m + -150m = -75m
43200 + -75m = 45450 + 150m + -150m

Combine like terms: 150m + -150m = 0
43200 + -75m = 45450 + 0
43200 + -75m = 45450

Add '-43200' to each side of the equation.
43200 + -43200 + -75m = 45450 + -43200

Combine like terms: 43200 + -43200 = 0
0 + -75m = 45450 + -43200
-75m = 45450 + -43200

Combine like terms: 45450 + -43200 = 2250
-75m = 2250

Divide each side by '-75'.
m = -30

Simplifying
m = -30

See similar equations:

| 10x^2+x+48=0 | | (6a+8)(a+4)= | | 23+x=40 | | 2(2x+6)=100 | | 282=n | | 7a-4=3b+5 | | -5y=-3x+12 | | 3x-11=x+32 | | m-2+4m/3=m/2 | | 9y=6x+11 | | (16a^4/25b^8)^3/2 | | 5x^2+6x=-5x-2 | | 3x-14=x+32 | | 2y=-5x+9 | | 5-2x+x-4=3 | | p=-4x^2+80x-200 | | -21(x-84)=x+47 | | 2.75(x-0.5)=2.6x | | 6x-28=2x+64 | | X-234=200 | | 2a-9.3=0.8a+51 | | F(X+8)=X^2+9X-3 | | 46r-11=62r-75 | | (7a^2b^3/3c^0)^-2 | | 9r-2-2-6r=1 | | -2x-2+3-7x= | | 10m+2n-5m+9n= | | (3x+2)=4x+5 | | 88(x-42)=x+47 | | 3(2x-12)=8(3x+9) | | (x-3)^1/2=6 | | 3x^2-4x=6x-3 |

Equations solver categories